Investigation of the causes of operational breakdowns in metallurgical equipment and vehicle parts produced by open die forging - Kukhar, V. V.; Vasylevskyi, O. V.; Shtuts, A. A.; Кухар, В. В. (Національний університет «Запорізька політехніка», 2025)
The most critical parts of metallurgical equipment and transport are made using metal forming, particularly open die forging. Their durability depends on key quality factors like dimensions, surface finish, mechanical properties, and structural integrity. The entire production cycle, including steel grade, ingot quality, heating, forging temperature, and heat treatment, significantly impacts the properties of forged products. Grain refinement is crucial for improving mechanical performance and operational reliability. This study examines the quality and technological parameters of forged components for metallurgical equipment and transport, aiming to identify failure causes, evaluate the influence of production methods on durability, and recommend strategies for enhancing performance.